GÜÇLENDİRİLMİŞ TABAKALI KOMPOZİT PANELLERDE DARBE SONRASI EZİLME DAVRANIŞININ İNCELENMESİ - USLU, MERVE (Fırat Üniveristesi, 2026)
Bu çalışma kapsamında, havacılık ve savunma sanayiinde kullanılan kompozit yapılarda darbe dayanımını ve darbe sonrası davranışı geliştirmek amacıyla farklı rijitlik yapılarına sahip güçlendirilmiş panel tasarımları incelenmiştir. Projede, kompozit paneller üzerinde sırasıyla darbe testleri ve darbe sonrası oluşan hasarın yapısal kararlılığa etkisini değerlendirmek için darbe sonrası ezilme testleri gerçekleştirilmiştir. Bu testler aracılığıyla panellerin enerji sönümleme kapasiteleri, hasar gelişim mekanizmaları ve artık yük taşıma kapasiteleri detaylı olarak analiz edilmiştir. Deneysel sürece ek olarak, panel davranışının doğrulanması amacıyla LS-DYNA sonlu elemanlar yazılımında sayısal modeller oluşturulmuş ve MAT162 kompozit malzeme modeli kullanılarak darbe ve darbe sonrası yükleme senaryoları simüle edilmiştir. Sayısal analizlerden elde edilen sonuçlar deneysel verilerle karşılaştırılarak modelin doğruluğu değerlendirilmiş; U-profil geometrisi, panel rijitliği ve lokal güçlendirme tasarımlarının darbe sonrası yapısal bütünlüğe etkisi ortaya konmuştur. Sonuçlar, uygun şekilde güçlendirilmiş panellerin hem darbe anında hem de darbe sonrası ezilme yükleri altında daha yüksek stabilite, daha düşük delaminasyon ve daha kontrollü bir hasar yayılımı sağladığını göstermektedir. Elde edilen bulgular, özellikle uçak gövde panelleri, İHA yapıları ve hafif zırh sistemleri gibi kritik uygulamalarda kompozit panel tasarımına önemli katkılar sunmaktadır.

In this study, various strengthened composite panel designs with different stiffness configurations were investigated to improve the impact resistance and post-impact performance of composite structures commonly used in the aerospace and defense industries. Within the scope of the project, impact tests were performed on composite panels, followed by post-impact crushing tests to evaluate the residual load-carrying capacity, energy absorption behavior, and damage progression mechanisms. These experiments provided a detailed understanding of both the immediate and subsequent structural responses of the panels under dynamic loading conditions. In addition to the experimental work, numerical models were developed using the LS-DYNA finite element software to validate the structural response of the panels. The MAT162 composite material model was employed to simulate both impact and post-impact loading scenarios. Numerical results were compared with experimental findings to assess model accuracy, and the effects of stringer geometry, panel stiffness, and local reinforcement strategies on the overall structural integrity were thoroughly examined. The results demonstrated that properly strengthened composite panels exhibit higher stability, reduced delamination, and a more controlled damage progression under both impact and post-impact crushing loads. These findings present significant advantages for critical applications such as aircraft fuselage panels, unmanned aerial vehicle structures, and lightweight protective systems. Overall, the project contributes valuable insights to the design and optimization of composite panels through a combined experimental–numerical approach.
Investigation of post impact crush behavior in stiffened layered composite panels
Keywords: Makine Mühendisliği